Rehabilitation project for residential use of the old abbey of Salas de Bureba (Burgos) - Paula Montoya-Saiz; Raul Briones-Llorente; Juan María Hidalgo-Betanzos; Imanol Ruiz-de-Vergara-Ruiz-de-Azúa; Gabriel Rubio-Pérez; Natalia Muñoz-Rujas; Fernando Aguilar-Romero (Anales de Edificación)
The rehabilitation of buildings is key to fighting climate change and offers opportunities to fix population in rural areas, revalue their heritage and help decongest cities. In addition, it has a lower environmental impact than new construction. With this contribution, the project for the rehabilitation of the old Abbey of Salas de Bureba, located in the Caderechas Valley, north of Burgos, is presented. The aim is to return the building to its original state, for which a study of construction pathologies has been carried out, applying the optimal solutions in each case, with a focus on energy efficiency and sustainability. After a detailed energy study, passive improvements combined with the installation of renewable energies have been proposed. This project, already in execution, has obtained a double A energy rating, which has allowed it to opt for aid from the PREE 5000 Program.